Isolation and Characterization of Novel Insertional Mutants in the Early Region 1A of Adenovirus Type 5 - Bautista, Diosdado S. (My University, 1989)
The early region 1A (E1A) of adenovirus 5 codes for oncoproteins whose functions are central to the life cycle of the virus. Its involvement in the initiation of the oncogenic transformation process has been a subject of intense study to understand the mechanism(s) of oncogenesis. To gain a better understanding of the structures of E1A proteins and their relationship to their various functions such as gene regulation and oncogenic transformation, a genetic study was undertaken. This involved mutagenesis of E1A by introducing a defined mutator DNA duplex into various sites in an E1A-containing plasmid specified by several multi-cut restriction enzymes. To facilitate the isolation and genotypic characterization of such mutants, a general method for introducing oligomers in the form of a cassette into multicopy plasmids was developed. This system had several attractive features. First, the mutator cassette contained the bacterial lac operator sequence as a phenotypic label permitting easy identification of clones with inserts. Second, the cassette was designed for sufficient flexibility to introduce any desired sequence. Third, it allowed fast and efficient sequencing of the plasmid with an insert to determine its orientation as well as the structure around the insert.
To mutate E1A, a 39-bp cassette was used that was capable of coding for 13aa residues in one orientation but was designed to terminate translation in the other orientation due to stop codons in each of the reading frames. It contained flanking BamHI sites that allowed 'collapsing' the insert to result in a net insert of two residues. A total of 18 sites in E1A have been mutated, each containing these three types of mutations. To determine the phenotypes of such mutants with respect to E1A's transcriptional regulatory functions (trans-activation and trans-repression), reporter genes with the bacterial β-galactosidase gene under the control of the adenovirus E1A, E1B and E3 promoters were constructed and used in co-transfection studies with the mutants in HeLa cells. The trans-activation assays showed that the unique region of the 13S E1A product was the only important domain for the activation of the E1A, E1B and E3 promoters as indicated by the finding that only insertions (both long and short) in this region abolished or diminished the expression of the reporter plasmids. However, while all long insertions in the unique region affected function, the shorter 2aa residue insertions had variable effects since one such mutant did not affect function, indicating that not only size but also the sequence of the insert could affect the trans-activation function.
The trans-repression assays were done using similar mutants modified so that only the 125 E1A product was expressed. This was necessary to prevent the interference in the assay by the trans-activation function found in the larger protein. The results showed that two regions flanking the unique region were sensitive to insertion mutations with respect to this function. Again perturbation of the sequence by size alone was not sufficient to destroy protein function but more important was the sequence of the insert. These regions are positioned adjacent to each other in the 12S product and most likely form a single domain for the trans-repression function.
Keywords: Biology